Migrants Are Underrepresented in Mental Health and Rehabilitation Services-Survey and Register-Based Findings of Russian, Somali, and Kurdish Origin Adults in Finland - Castaneda AE; Cilenti K; Rask S; Lilja E; Skogberg N; Kuusio H; Salama E; Lahti J; Elovainio M; Suvisaari J; Koskinen S; Koponen P (MDPI, 2022)
Mounting evidence suggests that migration background increases the risk of mental ill health, but that problems exist in accessing healthcare services in people of migrant origin. The present study uses a combination of register- and survey-based data to examine mental health-related health service use in three migrant origin populations as well as the correspondence between the need and use of services. The data are from the Finnish Migrant Health and Wellbeing Study (Maamu), a comprehensive cross-sectional interview and a health examination survey. A random sample consisted of 5909 working-aged adults of Russian, Somali, and Kurdish origin of which 3000 were invited to participate in the survey and the rest were drawn for a register-based approach. Some of the mental health services, based on registers, were more prevalent in the Kurdish origin group in comparison with the general population and less prevalent in the Russian and Somali origin groups. All the migrant origin groups were underrepresented in rehabilitation services. When affective symptoms were taken into account, all the migrant origin groups were underrepresented in all of the services. This calls for actions to promote mental health, diminish the barriers to access services, and improve the service paths for migrants.